Tingkat Kepercayaan Masyarakat terhadap Kinerja Polri Tahun 2021 - Azis Saputra (Jurnal Litbang Polri, 2022)
This research on the level of public trust in the performance of the Indonesian Police in 2021 aims to measure the level of public trust in the Police performance. It refers to the specific Police operational functions; Binmas, Intelkam, Lantas, Reskrim, and Sabhara. This study uses a mixed-method which is a combination of quantitative and qualitative. The quantitative method used is a survey with 44,516 respondents spread across 185 Polres in 34 Polda with a margin of error of 5%. The qualitative methods used are Focus Group Discussion (FGD) and in-depth interviews. This study indicates that the Indonesian National Police Public Trust Index (IKM) in 2021 is 83.14 in the Very Good category. Meanwhile, IKM Polri scores for each operational function; the Binmas function is 85.25; the Intelkam function is 80.99; the Lantas function is 83.53; the Reskrim function is 82.97, and the Sabhara function is 82.94. Based on the regression results on the questionnaire data, the factors that affect the IKM Polri in each operational function categorized into; a) excellent service, b) service needs improvement, c) service needs improvement. The perceptions and expectations of the community also vary. However, it shows that the community is very enthusiastic about the service programs provided by the Police. This program, such as the Bhabinkamtibmas approach with a religious and cultural basis, improving technological facilities and infrastructure in the service sector, increasing the ability to investigate cybercrimes in the digital era and patrols in vulnerable areas. On the other side, the internal police perspective has also made breakthroughs and innovations to increase public trust, such as optimizing the police presence in residential areas, applying technology in operational services, and forming special teams for crime prevention. However, Police still have obstacles, such as the limited number of personnel, limited technological facilities and infrastructure in the region, the lack of an orderly culture of community traffic, and the limited quality of investigators' human resources. Therefore, the recommendations given are adjusted from the regression results in each function categorized as 1) maintains excellent category services, 2) enhancing service categories that need to be enhanced, and 3) revitalizing services that need improvement.